Transcriptional and Post-transcriptional Regulation - Ghedira, Kais (IntechOpen, 2018)
This book focuses on the transcriptional and post-transcriptional gene regulations and presents a detailed portrait of many novel aspects related to highlighting the importance of key TFs in some vital biological processes, the role of certain TFs to control some infectious diseases, the role of non-coding RNAs in controlling mRNA expression, the involvement of these non-coding RNAs in diseases, and the interplay between TFs and microRNAs as key players for gene expression regulation giving a complete picture of how genes are regulated at the cellular level. The editor embarked upon this writing project entitled "Transcriptional and Post-transcriptional Regulation" to make pertinent contributions accessible to the scientific community. Hopefully, a large audience will enjoy reading and benefit from the chapters of this book.